Understanding Motivations and Barriers to Exercise among People with Blindness in India - India, Gesu; Jain, Mohit; Manohar, Swami (INTERACT 2021, 2021)
People with vision impairments (PVIs) have inferior physical fitness compared to sighted individuals. Several studies have been conducted to understand concerns, motivations, barriers, and experiences with exercise in the blind population. However, these studies have been limited to the developed regions. India is home to one-third of the world’s blind population and hence it is crucial to understand exercise patterns among PVIs in India. In this work, we interviewed 24 Indian PVIs to uncover novel insights, including minimal use of exercise technology, crucial role of blind schools, and infrastructural and social barriers. We conclude the paper with design recommendations, such as exploiting the design space of restricted walking, emphasizing on schools for the blind, and forming support groups to promote exercises among PVIs